POLITISASI IDENTITAS DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR SUMATERA UTARA TAHUN 2018 - Rizky Reynaldy Chaniago; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2020)
North Sumatra is one of the provinces that has held 2018 simultaneous local elections.This local election was attended by two pairs of candidates, namely Eramas and Djoss.Eramas won in the Regencies/Cities where the majority of the population was Muslim andnon-Batak ethnicity, while Djoss won in the Regencies/Cities where the majority of thepopulation was Christian and Batak ethnicity. In this case, it is thought that identitypoliticization took place in each process of the elections. The purpose of this research was todetermine the process of political dynamics in the 2018 North Sumatra Local Election and toidentify forms of identity politicization in the 2018 North Sumatra Local Election.This research uses descriptive qualitative method with data collection techniques throughinterviews and documentation. In this study, primary data obtained through direct interviewswith informants determined from the linkage of these informants with research problems, andsecondary data obtained from Provincial KPU Decisions and related articles. The researcherfocused the informants on the main party cadres supporting the two candidate pairs, namelythe Gerindra Party and the PDI-Perjuangan Party, political consultants, and local politicalobservers.The results of this study indicate that the process of identity politicization is carried outby both pairs of candidates. However, identity politicization carried out by Djoss is not asactive as what Eramas does. Eramas intensively provides stimulus to the community relatedto the issue of sons and daughters of religious issues, while the politicization of identitycarried out by Djoss was more about an abstark approach, there was no direct involvementin any activity, but only attended without initiating it.The process of identity politicization carried out by Eramas can be said to be theirstrategy in winning the 2018 North Sumatra Local Election. This is an adoption of thedynamics that occurred in the 2017 DKI Jakarta Local Election, while identity politicizationdone by Djoss is a common thing as a complement to their vision and mission to build NorthSumatra. It is expected that each pair of candidates will prioritize socialization to the publicabout the vision and mission and superior programs that will be carried out in developing theregion for the next period and to the next researcher, is expected to interview and explore asmuch information as possible to key informants.Keywords: The 2018 North Sumatra Local Election, Politicization of Identity, Ethnicity,Religion